Dry eye or contact lens?. Issue 8 (August 2020) - Gibson, Tony
Abstract : As part of our series, developed with Alcon, Dr Tony Gibson presents a case of dry eye in a contact lens wearer who mistakenly believed her symptoms to be solely due to the contact lenses